Application of PD-1 Blockade in Cancer Immunotherapy - Wu, Xiaomo; Gu, Zhongkai; Chen, Yang; Chen, Borui; Chen, Wei; Weng, Liqiang; Liu, Xiaolong (Computational and structural biotechnology journal, 2019)
The programmed cell death protein 1 (PD-1) pathway has received considerable attention due to its role in eliciting the immune checkpoint response of T cells, resulting in tumor cells capable of evading immune surveillance and being highly refractory to conventional chemotherapy. Application of anti-PD-1/PD-L1 antibodies as checkpoint inhibitors is rapidly becoming a promising therapeutic approach in treating tumors, and some of them have successfully been commercialized in the past few years. However, not all patients show complete responses and adverse events have been noted, suggesting a better understanding of PD-1 pathway mediated immunosuppression is needed to predict patient response and improve treatment efficacy. Here, we review the progresses on the studies of the mechanistic role of PD-1 pathway in the tumor immune evasion, recent clinical development and commercialization of PD-1 pathway inhibitors, the toxicities associated with PD-1 blockade observed in clinical trials as well as how to improve therapeutic efficacy and safety of cancer immunotherapy. [Display omitted]